How does the BAPM Framework for Practice on Perinatal Management of Extreme Preterm Birth Before 27 Weeks of Gestation impact delivery of Newborn Life Support? A Resuscitation Council UK response. Issue 6 (9th April 2020) - Fawke, Joe; Tinnion, Robert J; Monnelly, Victoria; Ainsworth, Sean B; Cusack, Jonathan; Wyllie, Jonathan
Abstract : In October 2019, the British Association of Perinatal Medicine (BAPM) published a Framework1 and associated infographic2 for ' Practice on Perinatal Management of Extreme Preterm Birth Before 27 Weeks of Gestation' . This outlined an approach, based on data from the UK and abroad, to assist clinicians in decision-making relating to perinatal care at ≤26 +6 weeks gestation. Many frontline providers of delivery room care of extremely preterm infants will have completed a Resuscitation Council UK (RCUK) Newborn Life Support or Advanced Resuscitation of the Newborn Infant course. This RCUK response to the BAPM Framework highlights how this might impact on their approach.